2015
DOI: 10.1007/s13277-015-3231-7
|View full text |Cite
|
Sign up to set email alerts
|

3B, a novel of photosensitizer, exhibited anti-tumor effects via mitochondrial apoptosis pathway in MCF-7 human breast carcinoma cells

Abstract: Photodynamic therapy (PDT) has been recognized as an innovated therapeutic modality for the treatment of various cancers. In this study, we evaluated the anticancer effect of a new photosensitizer 3B in breast cancer, which was considered one of the most common cancers in women worldwide. Here, we determined the effect of 3B not only on the cell growth, apoptosis, and Bcl-2 signal pathway in vitro but also on the anti-cancer effect in nude mice in vivo. Our results showed that 3B was primarily accumulated in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…JAK/STAT signal transduction pathway can promote the expression of many downstream growth factors [such as vascular endothelial growth factor A (VEGFA), insulin-like growth factor-1 and matrix metalloproteinase], and can activate, as well as promote, angiogenesis at the tumor site, thus promoting cell proliferation and survival and inhibiting apoptosis (1012). In addition, JAK/STAT signal transduction pathway also plays regulatory roles in glycolysis, inflammatory response and epithelial mesenchymal transformation (13,14). However, the regulation processes of apoptosis, glycolysis, inflammatory response, epithelial mesenchymal transformation and angiogenesis, by the JAK/STAT signal transduction pathway are accompanied by tumor cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…JAK/STAT signal transduction pathway can promote the expression of many downstream growth factors [such as vascular endothelial growth factor A (VEGFA), insulin-like growth factor-1 and matrix metalloproteinase], and can activate, as well as promote, angiogenesis at the tumor site, thus promoting cell proliferation and survival and inhibiting apoptosis (1012). In addition, JAK/STAT signal transduction pathway also plays regulatory roles in glycolysis, inflammatory response and epithelial mesenchymal transformation (13,14). However, the regulation processes of apoptosis, glycolysis, inflammatory response, epithelial mesenchymal transformation and angiogenesis, by the JAK/STAT signal transduction pathway are accompanied by tumor cell metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription was performed with ReverTra Ace qPCR RT Kit (Toyobo, Japan), and primers were designed and purchased from Sangon Biotech. Real-time PCR was performed with tests were performed in triplicate [27].…”
Section: Validation Of the Expression In Degs In Q-pcrmentioning
confidence: 99%
“…Sensitivity to ROSinduced oxidative stress vary from one cancer cell to another (21,22). Therefore, elevated ROS levels stimulated by anticancer drugs leads to the induction of apoptosis in the cell (11). It has been reported that ROS promote degradation of CAV-1 via the proteasome system which in turn enhances the proliferation and migration of lung cancer cells (12).…”
Section: Discussionmentioning
confidence: 99%
“…An understanding of their interaction may offer a novel strategy for treatment of ESCC and improvement of clinical outcomes. The accumulation of ROS regulates the proliferation and apoptosis of tumor cells (11). Caveolin-1 (CAV-1) promotes the proliferation and migration of lung cancer cells via a mechanism involving the PI3K/Akt pathway.…”
Section: Introductionmentioning
confidence: 99%